Theories of Change for Promoting Empowerment and Accountability in Fragile and Conflict-Affected Settings - Green, Duncan (IDS, 2017)
This paper explores the current state of thinking among a range of aid actors (multilaterals, bilateral, applied scholars and international non-governmental organisations) on how to promote empowerment and accountability in fragile, conflict and violence affected settings. It seeks to identify trends, gaps and weaknesses in that thinking, and propose research questions and hypotheses to test. Three underlying sources of confusion are identified that are hindering progress on both understanding empowerment and accountability in fragile, conflict and violence affected settings, and taking helpful action to promote it. They are: (1) theory of endogenous change (e.g. on how empowerment and accountability arise in situ) versus the theory of action of an external intervention; (2) fragility versus conflict: there is no clear justification for combining these different aspects into a single category; and (3) empowerment versus accountability: donor analysis and practice has been overwhelmingly weighted towards accountability, exhibiting limited understanding or interest in the nature of power.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; conflict / conflito; empowerment / empoderamento; fragility / fragilidade

AGORA ELES TÊM MEDO DE NÓS! Uma colectânea de textos sobre as revoltas populares em Moçambique (2008–2012 - Brito, Luís de (IESE, 2017)
A presente colectânea reúne uma série de textos de natureza diferente, mas que tratam todos da mesma temática, as revoltas populares do final da primeira década dos anos 2000 em Moçambique. Partindo de diferentes disciplinas das ciências sociais e de abordagens teóricas diferenciadas, todos têm em comum a intenção de contribuir para a compreensão não só das causas e dos elementos desencadeadores das manifestações populares violentas, mas sobretudo do seu significado mais profundo no actual tecido económico, político e social moçambicano. Sem pretender esgotar o rico conteúdo dos capítulos, apresentamos de seguida e em forma muito parcial e resumida alguns dos aspectos que merecem destaque em cada um deles.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza